2020 Jolo suicide attack : evolving tactics - Yeo, Kenneth (2020)
The 24 August 2020 suicide bombing in Jolo which involved female attackers has brought attention to the emergence of the pro-Islamic State (IS) Hatib Hajan Sawadjaan faction of the Abu Sayyaf Group and its tactic of engaging women for this role.